Frequency Of Left Ventricular Thrombi In Dilated Cardiomyopathy Patients Presenting In Tertiary Care Hospital Of Punjab - Tahira Nazir; Tehreem Amjad; Madiha Fayyaz; Somayya Siddiqa; Sobia Naveed; Shahroon Zahid (Journal of Rawalpindi Medical College)
Objective: This study has been carried out to determine the frequency of left ventricular thrombi in dilated cardiomyopathy patients presenting in tertiary care hospitals in Punjab.